Antara Sakral dan Profan: Analisis Dikotomi Durkheim dan Simbolisme Geertz dalam Ritual Hoyak Tabuik - Riska Ramadhani (Yayasan Al-Afif, 2025)
This study examines the sacred–profane relationship in the Tabuik tradition of Pariaman, which combines ritual mourning over the Karbala tragedy, popular festivity, intergroup rivalry, and tourism commercialization. Its aims are: (1) to analyze the construction of the sacred dimension through the separation of space and time, initial rituals, and Tabuik symbolism; (2) to explain the emergence of the profane dimension through Hoyak Tabuik, the rivalry between Tabuik Pasa and Tabuik Subarang, and economic–tourism integration; and (3) to examine the synthesis of sacred–profane tensions in the casting of the Tabuik into the sea. The study employs a descriptive qualitative approach with cultural ethnography through participant observation, in-depth interviews, and documentation studies, thematically analyzed using the theories of Durkheim, Geertz, Simmel, and Coser. The findings show that Tabuik is a socio-religious practice that dynamically negotiates the sacred–profane boundary while simultaneously renewing community social cohesion.